module Cat.Displayed.Total.Op where
open Functor
open Total-hom
Total opposites🔗
Opposites of displayed categories are somewhat subtle, as there are multiple constructions that one could reasonably call the “opposite”. The most obvious construction is to construct a new displayed category over we call this category the total opposite of
module _ {o ℓ o' ℓ'} {ℬ : Precategory o ℓ} (ℰ : Displayed ℬ o' ℓ') where
open Precategory ℬ
open Displayed ℰ
_^total-op : Displayed (ℬ ^op) o' ℓ'
_^total-op .Displayed.Ob[_] x = Ob[ x ]
_^total-op .Displayed.Hom[_] f x y = Hom[ f ] y x
_^total-op .Displayed.Hom[_]-set f x y = Hom[ f ]-set y x
_^total-op .Displayed.id' = id'
_^total-op .Displayed._∘'_ f' g' = g' ∘' f'
_^total-op .Displayed.idr' f' = idl' f'
_^total-op .Displayed.idl' f' = idr' f'
_^total-op .Displayed.assoc' f' g' h' = symP $ assoc' h' g' f'
Much like the opposite of categories, the total opposite is an involution on displayed categories.
total-op-involution: ∀ {o ℓ o' ℓ'} {ℬ : Precategory o ℓ} {ℰ : Displayed ℬ o' ℓ'}
→ (ℰ ^total-op) ^total-op ≡ ℰ
{ℰ = ℰ} = path where
total-op-involution open Displayed
: (ℰ ^total-op) ^total-op ≡ ℰ
path .Ob[_] = ℰ .Ob[_]
path i .Hom[_] = ℰ .Hom[_]
path i .Hom[_]-set = ℰ .Hom[_]-set
path i .id' = ℰ .id'
path i ._∘'_ = ℰ ._∘'_
path i .idr' = ℰ .idr'
path i .idl' = ℰ .idl'
path i .assoc' = ℰ .assoc' path i
The total opposites and total categories🔗
The reason we refer to this construction as the total opposite is that its total is equal to the opposite of the total category! To show this, we first need to prove some lemmas relating the morphisms of the total category of the total opposite to those in the opposite of the total category. These functions are essentially the identity function, but we can’t convince Agda that this is the case due to definitional equality reasons.
total-op→total-hom: ∀ {o ℓ o' ℓ'} {ℬ : Precategory o ℓ} {ℰ : Displayed ℬ o' ℓ'}
→ ∀ {x y} → Total-hom (ℰ ^total-op) x y → Total-hom ℰ y x
= total-hom (f .hom) (f .preserves)
total-op→total-hom f
total-hom→total-op: ∀ {o ℓ o' ℓ'} {ℬ : Precategory o ℓ} {ℰ : Displayed ℬ o' ℓ'}
→ ∀ {x y} → Total-hom ℰ y x → Total-hom (ℰ ^total-op) x y
= total-hom (f .hom) (f .preserves) total-hom→total-op f
Furthermore, these two maps constitute an equivalence, and thus yield an equality of types via univalence.
total-op→total-hom-is-equiv: ∀ {o ℓ o' ℓ'} {ℬ : Precategory o ℓ} {ℰ : Displayed ℬ o' ℓ'}
→ ∀ {x y} → is-equiv (total-op→total-hom {ℰ = ℰ} {x = x} {y = y})
=
total-op→total-hom-is-equiv (λ _ → refl) (λ _ → refl)
is-iso→is-equiv $ iso total-hom→total-op
total-op≡total-hom: ∀ {o ℓ o' ℓ'} {ℬ : Precategory o ℓ} {ℰ : Displayed ℬ o' ℓ'}
→ ∀ {x y} → Total-hom (ℰ ^total-op) x y ≡ Total-hom ℰ y x
= ua $ total-op→total-hom , total-op→total-hom-is-equiv total-op≡total-hom
We can use the fact that total-op→total-hom
is an equivalence to
construct an isomorphism of precategories.
∫total-op→∫^op: ∀ {o ℓ o' ℓ'} {ℬ : Precategory o ℓ} (ℰ : Displayed ℬ o' ℓ')
→ Functor (∫ (ℰ ^total-op)) ((∫ ℰ) ^op)
_ .F₀ x = x
∫total-op→∫^op _ .F₁ f = total-op→total-hom f
∫total-op→∫^op _ .F-id = refl
∫total-op→∫^op _ .F-∘ _ _ = refl
∫total-op→∫^op
∫total-op≅∫^op: ∀ {o ℓ o' ℓ'} {ℬ : Precategory o ℓ} (ℰ : Displayed ℬ o' ℓ')
→ is-precat-iso (∫total-op→∫^op ℰ)
.is-precat-iso.has-is-ff = total-op→total-hom-is-equiv
∫total-op≅∫^op ℰ .is-precat-iso.has-is-iso = id-equiv ∫total-op≅∫^op ℰ
Finally, we show that this extends to an equality of categories.
∫total-op≡∫^op: ∀ {o ℓ o' ℓ'} {ℬ : Precategory o ℓ} (ℰ : Displayed ℬ o' ℓ')
→ ∫ (ℰ ^total-op) ≡ (∫ ℰ) ^op
=
∫total-op≡∫^op ℰ
Precategory-path(∫total-op→∫^op ℰ)
(∫total-op≅∫^op ℰ)
Functors between fibres🔗
If there is a functor between the fibres of a displayed category then we also obtain a functor between the fibres of the total opposite of
fibre-functor-total-op: ∀ {o ℓ o' ℓ'} {ℬ : Precategory o ℓ} {ℰ : Displayed ℬ o' ℓ'} {x y}
→ Functor (Fibre ℰ x) (Fibre ℰ y)
→ Functor (Fibre (ℰ ^total-op) x) (Fibre (ℰ ^total-op) y)
.F₀ = F .F₀
fibre-functor-total-op F .F₁ = F .F₁
fibre-functor-total-op F .F-id = F .F-id
fibre-functor-total-op F {ℰ = ℰ} F .F-∘ f g =
fibre-functor-total-op (F .F₁) (DR.reindex ℰ _ _ ) ·· F .F-∘ g f ·· DR.reindex ℰ _ _ ap